Answer:
If you wanted to simplify the equation.
3x - 4 = 5x - 6
If you wanted to solve for x.
x = 1
Explanation:
3(x+2)-10=4x-6+x
3x + 6 - 10 = 4x-6+x
3x - 4 = 4x - 6 + x
3x - 4 = 5x - 6
If you wanted to simplify the equation this is it. If you wanted to solve for x, continue reading.
Add 4 to both sides of the equation.
3x - 4 + 4 = 5x - 6 + 4
Simplify.
3x = 5x - 6 + 4
3x = 5x - 2
Subtract 5x from both sides of the equation.
3x - 5x = 5x - 5x - 2
Simplify.
-2x = 5x - 5x - 2
-2x = -2
Divide both sides of the equation by the same term.
(-2x/2) = (-2/2)
Cancel terms that are in both the numerator and denominator.
x = (-2/-2)
Divide the numbers.
x = 1